Techno-Economic Feasibility of Reverse Osmosis Desalination Scale Coupled with Solar Energy: Case of Algeria - Asma Adda; Salah Bezari; Mohamed Abbas; Salah Hanini (The Journal of Engineering and Exact Sciences)
B